Lecturer Performance Software Using the MOORA Method at IAIN Ash-Shiddiqiyah - Nurmadhani, Yosep; Mirza, A. Haidar (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
The importance of having an effective decision support system to select and determine the best lecturers cannot be denied. This research aims to develop a decision support system for selecting the best lecturers at IAIN ASH-SHIDDIQIYAH. The method used is MOORA (Multi-Objective Optimization on the basis of Ratio Analysis), a multi-objective approach that allows optimization of two or more conflicting attributes simultaneously. The results of this study include the development of a decision support system that can provide useful guidance for decision-makers at IAIN ASH-SHIDDIQIYAH in the process of selecting and determining the best lecturers. Through MOORA analysis, the best lecturers can be selected by considering various aspects such as teaching quality, research ability, contribution to curriculum development, involvement in guidance and training activities, and contribution to the community. The results of this research are expected to improve the quality of education and the institution's contribution to society as a whole through the selection of high-quality and high-performing lecturers. This research demonstrates that the development of a decision support system using the MOORA method can be an effective tool for higher education institutions in selecting the best lecturers.